POLICY OF LIMITATION OF MARRIAGE MINIMUM AGE ON MARRIAGE LAW REVISION BASED ON SOCIOLOGICAL AND ANTHROPOLOGICAL APPROACHES - Robiatul Adawiyah; Esmi Warassih Pudjirahayu (Fakultas Hukum, Universitas Diponegoro, 2021)
The policy of limitation of marriage minimum age is regulated by the government through the Marriage Law and have been revised. The struggle to determine the marriage minimum age has basically been debated for quite a long and time even each country determines these limits differently depending on problem needs and social realities that develop in the community. Therefore, this research is very important to do based on a sociological and anthropological approaches. The research purpose is to analisyst the minimum marriage age policy in the Marriage Law revision based on a sociological and anthropological approaches. The research method used socio-legal research. According to research, the minimum marriage age policy on the revision of the Marriage Law based on a sociological and anthropological approaches is not support the new norm and difficult to be effective and even cause a new impact, which is increasing marriage dispensation, depriving the right to continue marriage, and being criminogen factor.